To compare serum Vitamin D status in pre-eclamptic and non-preeclamptic pregnant women in labour: A tertiary care centre study of Northern India - Karpa, Monica; Thakur, Sita; Singh, Kamal; Sharma, Jyoti; Chaudhary, Harsha (Clinical Journal of Obstetrics and Gynecology, 2022)
Background: Pre-eclampsia and eclampsia have remained a major global public health threat in contributing significantly to maternal and perinatal morbidity and mortality. Based on the inverse relationship between serum 1,25(OH)2D3 levels and plasma renin activity found previously, it is speculated that 1,25(OH)2D3 might be a negative endocrine regulator of renin production in vivo. During pregnancy, vitamin D may play a role in implantation and placental function potentially due to angiogenic, immunomodulatory, and antiinﬂammatory effects. Vitamin D deficiency can affect the health of both mother and fetus by increasing the production of inflammatory cytokines and stimulating the activity of T-regulating cells. Vitamin D is emerging as a promising agent for pre-eclampsia prevention. Aims and objectives: The objective of this study is to compare the vitamin D levels in pre-eclamptic and healthy non-pre-eclamptic pregnant women in labor and find out the relationship between vitamin D levels and pre-eclampsia. Methodology: The present cross-sectional study was carried out on pregnant women with pre-eclampsia in labor. For each case with pre-eclampsia, one uncomplicated, normotensive pregnant woman in labor was taken as control. On admission to the labor room detailed history, physical examination followed by thorough obstetrics and systemic examination was done. Required investigations were done including vitamin D and calcium levels. Maternal and fetal condition was monitored during labor/cesarean section, mode of delivery, maternal and fetal outcomes were recorded. After delivery, 2cc of cord blood was collected in a serum tube and sent for vitamin D levels. Data was collected and analyzed statistically using Epi-info version 7.1. Results: It was observed that the patients in both groups were comparable with respect to demographic and obstetrics characteristics except for significantly high BP in group I. Vitamin D deficiency (i.e. < 20 ng/ml) was significantly more in group I as compared to group II and the difference was highly significant (p < 0.0001). Similarly, the mean maternal calcium levels were significantly lower in group I in comparison to group II (p < 0.0001) i.e. the mean maternal calcium level in group I and group II were 8.03 ± 0.94 and 9.19 ± 0.67 respectively. It was also observed that the level of 25-OH-D in neonates of preeclamptic women was significantly lower than for those of the normal pregnant women (p < 0.0001). Conclusion: Vitamin D deficiency is highly prevalent in all parts of the world. Pregnant women and neonates are highly vulnerable to vitamin D deficiency. Preeclampsia is indeed associated with lower vitamin D levels and the pathophysiology of pre-eclampsia involves vitamin D and calcium metabolism through their role in immunomodulation, angiogenesis and anti-inflammatory effects. From the present study, it was observed that vitamin D and calcium levels were significantly lowered in women with pre-eclampsia as compared to those of the normotensive pregnant women. So early detection of vitamin D and calcium deficiencies may be helpful in preventing occurrence of PET and its complications.